Plasma Platform to Investigate Error Structure in the Electronic Components - M.V., Roshan; H., Sadeghi; S., Fazelpour; Lee, S.; Yap, S. L. (IEEE, 2019)
This program was designed to introduce a plasma platform to examine the field programmable gate array (FPGA) of the link boards typically used at the CERN's Large Hadron Collider (LHC). Pulsed plasma systems with accelerating gradient of 1 kV/μm generate high-intensity, high-energy radiation beams. Single-event upset (SEU) is caused by radiation deposition in the FPGA. In FPGA, the SEU probability for 1-MeV protons and 10-keV X-rays are 0.1 and 2×10 -9 particle -1 . The number of SEU induced in the Si by 1-MeV proton irradiation at 0.8-V bias computed from simulation in COMSOL Multiphysics was 1.8 × 10 5 . Although more experimental research is needed to identify the underlying mechanisms, pulsed plasma is perceived as being a smart alternative to investigate the error structure in FPGA.